Potensi Pengelolaan Zakat Produktif pada Daarut Tauhid (DT) Peduli Kota Jambi - M. Nazori; Agustina Mutia; Priska Yunita (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
The results of this study indicate that DT Peduli Jambi has not yet fully optimized the management of productive zakat, despite having a structured management system in place. Based on data analysis, several key factors were identified as obstacles to optimization. First, there is a lack of public trust in the institution, as reflected in the absence of significant growth in zakat collection over the past three years. This condition highlights the need for more effective communication and transparency strategies. Second, administrative challenges remain, such as a record-keeping system that is not yet fully integrated digitally and limited human resources with expertise in managing productive zakat. Third, resistance to change among beneficiaries persists, with approximately 30% refusing to adopt modern business management methods offered by the program. Fourth, there is a high dependency on assistance, with 40% of beneficiaries still heavily reliant on institutional mentoring. Fifth, participation in training programs remains low, with an average attendance rate of only 65%. Nevertheless, overall the program is categorized as “fairly successful” with an achievement score of 70 out of 100. This indicates that productive zakat holds great potential to promote economic empowerment of the community but has not yet been maximized due to structural and cultural barriers. Therefore, improvements are needed in transparency, capacity building of human resources, as well as persuasive and participatory approaches for beneficiaries, so that the goal of economic empowerment through productive zakat can be more effectively realized.